Internationale Studienergebnisse (Praxis Handreha, 2021)
Gladitz LM, Schöttker-Königer T, Sturm C et al. The flexor pollicis longus reflex. Interrater and intrarater reliability in comparison with established muscle stretch reflexes. Am J Phys Med Rehabil 2021; 100: 539–545